Preparation method of manganese-based catalyst, prepared catalyst and application
By growing manganese-based active components in situ on a support with a connecting channel, combined with 3D printing and hydrothermal reaction technology, the problems of limited loading of active components and high cost of precious metal catalysts in the prior art are solved, and high catalysis is achieved Oxidation activity and low-cost catalyst.
Patent Information
- Application Number
- CN202311031994.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-16
AI Technical Summary
In the prior art, the loading amount of active components on the carrier of a conventional one-dimensional array honeycomb channel structure is limited, resulting in limited contact between the active components in the catalyst and the catalytic oxidation reactants, and the cost of noble metal catalysts is high, which limits its industrial use. Promotion and use of the world.
Through in-situ growth method, manganese-based active components are loaded on the carrier with a connecting channel, so as to achieve single flexible control of the load of the active components. The carrier is prepared by 3D printing technology, combining hydrothermal reaction and calcination process to form a uniform load A catalyst for manganese-based active components.
The catalytic oxidation activity of the catalyst is improved, the cost of the catalyst is reduced, the loading procedure of the active component is simplified, and the three-dimensional communication channel structure of the 3D printing support improves the reaction contact conditions and improves the atomic utilization efficiency of the active component.
Smart Images

Figure CN119488917A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalytic materials, and in particular to a method for preparing a manganese-based catalyst, and the prepared catalyst and application thereof. Background Art
[0002] Volatile organic compounds (VOCs) are organic compounds with a saturated vapor pressure higher than 133.32 Pa and a boiling point between 50-250°C. x and VOCs are atmospheric PM 2.5 and an important precursor of near-surface O3, along with NO x The effect of emission reduction is gradually showing, and the sensitivity of O3 pollution control to VOCs control has increased significantly. VOCs have become the key to solving the problem of regional atmospheric complex pollution. Industrial source VOCs emission control is still the current focus of work. Commonly used technologies include recovery technologies represented by adsorption and absorption, and destruction technologies represented by catalytic oxidation and thermal storage combustion. Among them, the catalytic oxidation method has broad application prospects due to its advantages such as high treatment efficiency, low secondary pollution, and strong equipment compatibility. At present, most of the catalysts that have been commercialized are honeycomb monolithic catalysts with cordierite and honeycomb ceramics as carriers, and their surfaces are coated with Al2O3, rare earth modified oxides, etc. and coupled with precious metal active components such as Pd and Pt.
[0003] Although the traditional honeycomb monolithic catalyst has stable VOCs oxidation performance and industrial operation effect, the catalyst utilization efficiency is not high, which indirectly increases the cost of catalyst use. In the process of coating the active components of the catalyst, in order to increase the coating amount, it is usually necessary to prepare a catalyst slurry with suitable physical and chemical properties, and then go through repeated coating, drying and other processes to produce the target monolithic catalyst. On the other hand, the high cost of commercial precious metal catalysts has always limited their further promotion and use in the industry, and the research and development of high-performance, low-cost alternative materials has become an urgent need.
[0004] 3D printing technology is a new type of intelligent manufacturing technology that uses computer-controlled material stacking to form a three-dimensional target structure. Hajimirzaee et al. used computational fluid dynamics analysis to confirm that 3D printed carriers significantly increase the turbulence of the airflow, turbulence / mass transfer and surface area (Fuel, 2020, 274: 117848), indicating that the characteristics of 3D printed carriers have outstanding application potential in catalysts. However, how to combine 3D printed carriers with active components to improve the application of 3D printed carriers in the field of VOCs catalytic oxidation still needs to be overcome. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems in the prior art that the loading amount of active components on a carrier with a conventional one-dimensional array honeycomb pore structure is limited, and the contact between the active components in the catalyst and the catalytic oxidation reactants is limited. A method for preparing a manganese-based catalyst, a prepared catalyst and an application thereof are provided. The method loads the manganese-based active components on a carrier with connected pores by an in-situ growth method, realizes a single flexible control of the loading amount of the active components, has the advantages of simple operation and strong controllability, obtains a catalyst uniformly loaded with manganese-based active components, can effectively improve the catalytic oxidation activity of the prepared catalyst, and reduces the cost of the catalyst.
[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a manganese-based catalyst, comprising the following steps: subjecting a structured carrier to a hydrothermal reaction in a manganese-based precursor dispersion, and calcining to obtain a manganese-based catalyst;
[0007] The manganese-based precursor dispersion comprises a manganese salt, an optional soluble salt of M metal and a solvent, and a precipitation aid is optionally added; the M metal element is selected from at least one of Fe, Co, Ni, Cu and Ce.
[0008] The second aspect of the present invention provides a manganese-based catalyst, wherein the catalyst comprises a regular carrier and an active component layer loaded on the surface of the regular carrier, wherein the active component layer comprises a manganese compound and an optional M metal;
[0009] Preferably, the M metal element is selected from at least one of Fe, Co, Ni, Cu and Ce.
[0010] A third aspect of the present invention provides a method for preparing a manganese-based catalyst by 3D printing, which comprises the following steps:
[0011] (1) mixing a photosensitive resin mixed liquid with a ceramic powder to obtain a photosensitive ceramic slurry, and performing 3D printing to obtain a printed body;
[0012] (2) degreasing and sintering the printed body to obtain a 3D printed ceramic carrier;
[0013] (3) subjecting the 3D printed ceramic carrier to a hydrothermal reaction in a manganese-based precursor dispersion and calcining to obtain a manganese-based catalyst.
[0014] Preferably, the conditions of the hydrothermal reaction include: reaction temperature of 90-160° C., preferably 110-140° C.; reaction time of 12-24 h, preferably 12-18 h.
[0015] Preferably, in step (3), a precipitation aid is also added to the hydrothermal reaction, and the ratio of the total molar amount of Mn and M metal to the molar amount of the precipitation aid is 1:1-2.5, preferably 1:1.4-2.
[0016] The fourth aspect of the present invention provides a manganese-based catalyst prepared by the method described in the third aspect;
[0017] Preferably, the manganese-based catalyst comprises a 3D printed ceramic carrier and a manganese-based active component in situ grown on the 3D printed ceramic carrier.
[0018] The fifth aspect of the present invention provides a use of the manganese-based catalyst described in the second aspect or the fourth aspect in a catalytic oxidation reaction.
[0019] The preparation method provided by the present invention has the following beneficial effects:
[0020] (1) In the present invention, the manganese-based active component is loaded on the surface of the regular carrier by in-situ growth, so that the active component layer is loaded once, and the loading amount of the active component can be flexibly controlled. A higher amount of manganese-containing loading layer can be obtained by a single loading, which simplifies the catalyst active component loading procedure and can be used to prepare a catalyst with a high active component loading amount;
[0021] (2) In the present invention, preferably, the carrier obtained by 3D printing has a three-dimensional interconnected pore structure and a vertically staggered cross-pore structure. The interconnected pores of the carrier can fully expose the surface manganese-based active components. Under the same loading amount, the obtained catalyst can have a higher catalytic oxidation activity, which can effectively alleviate the problems of uneven airflow distribution and insufficient residence time of flue gas in the catalyst pores, improve the reaction contact conditions, and improve the atomic utilization efficiency of the active components, thereby improving the VOCs catalytic oxidation activity of the obtained catalyst;
[0022] (3) In the present invention, preferably, manganese-based active components are used to replace precious metal active components to be loaded on the carrier surface, which effectively reduces the cost of the catalyst and can be extended to the active component loading process on the carrier surface of a fixed bed catalyst system, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the 3D printed model structure in Example 1;
[0024] Figure 2 This is a physical photo of the manganese-based catalyst prepared in Example 1. DETAILED DESCRIPTION
[0025] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0026] The first aspect of the present invention provides a method for preparing a manganese-based catalyst, comprising the following steps: subjecting a structured carrier to a hydrothermal reaction in a manganese-based precursor dispersion, and calcining to obtain a manganese-based catalyst;
[0027] The manganese-based precursor dispersion comprises a manganese salt, an optional soluble salt of M metal and a solvent, and a precipitation aid is optionally added; the M metal element is selected from at least one of Fe, Co, Ni, Cu and Ce.
[0028] In the present invention, the regular carrier has the conventional meaning in the art, and refers to a carrier with a regular external and internal structure whose overall size can be determined, and which has high mechanical stability and specific surface area. The material of the regular carrier is not particularly limited, and those skilled in the art can select a material suitable for preparing a catalyst as a regular carrier, preferably a ceramic-based regular carrier. In the present invention, the source of the regular carrier is not particularly limited, and it can be commercially available or prepared by an existing method, as long as the properties of the regular carrier meet the preparation conditions of the manganese-based catalyst.
[0029] In the present invention, unless otherwise specified, the term "optional" means containing or not containing, adding or not adding, using or not using. Specifically, the term "optional M metal soluble salt" in the present invention means that the M metal soluble salt may be added or not added.
[0030] According to the present invention, preferably, the conditions of the hydrothermal reaction include: reaction temperature of 90-160° C., preferably 110-140° C.; reaction time of 12-24 h, preferably 12-18 h.
[0031] According to the present invention, preferably, the volume ratio of the structured support to the manganese-based precursor dispersion is 1:8-20, preferably 1:9-15.
[0032] In the present invention, the composition and content of the manganese-based precursor dispersion and the amount of precipitation aid added are as described below and will not be repeated here.
[0033] According to the present invention, preferably, the precipitation aid is selected from at least one of easily hydrolyzable organic amines, soluble carbonates and soluble bicarbonates, preferably selected from at least one of urea, NH4HCO3 and (NH4)2CO3.
[0034] The second aspect of the present invention provides a manganese-based catalyst, wherein the catalyst comprises a structured carrier and an active component layer loaded on the surface of the structured carrier, and the active component layer comprises a manganese compound and an optional M metal.
[0035] According to the present invention, preferably, the M metal element is selected from at least one of Fe, Co, Ni, Cu and Ce.
[0036] According to the present invention, preferably, based on the volume of the structured carrier as 1 L, the content of the active component layer on the surface of the structured carrier is 30-150 g / L, preferably 50-140 g / L.
[0037] According to the present invention, preferably, the molar ratio of Mn to M metal in the active component layer is 1:0-1, preferably 1:0.02-0.3.
[0038] In the present invention, the prepared manganese-based catalyst has a high loading amount of the active component layer on the surface of the regular carrier, and the loading amount of the active component can be flexibly controlled. The manganese-based catalyst has high catalytic oxidation activity.
[0039] In the present invention, the content of the manganese-based active component layer is calculated by the mass difference between the calcined catalyst and the original carrier.
[0040] A third aspect of the present invention provides a method for preparing a manganese-based catalyst by 3D printing, which comprises the following steps:
[0041] (1) mixing a photosensitive resin mixed liquid with a ceramic powder to obtain a photosensitive ceramic slurry, and performing 3D printing to obtain a printed body;
[0042] (2) degreasing and sintering the printed body to obtain a 3D printed ceramic carrier;
[0043] (3) subjecting the 3D printed ceramic carrier to a hydrothermal reaction in a manganese-based precursor dispersion and calcining to obtain a manganese-based catalyst.
[0044] In the present invention, a manganese-based active component is loaded on the surface of a 3D printed ceramic carrier in an in-situ growth manner. The manganese-based active component has strong redox properties and is loaded on the carrier. After the interaction during the roasting process, the catalytic activity and mechanical strength of the catalyst are improved. The method can achieve a single flexible control of the loading amount of the manganese-based active component. After the roasting treatment, a manganese-based catalyst is obtained, which can replace a precious metal catalyst and has good catalytic oxidation activity. The channels connected to the carrier can effectively alleviate the problem of uneven airflow distribution and insufficient residence time of flue gas in the catalyst channels.
[0045] In the present invention, preferably, the carrier prepared by 3D printing has three-dimensional interconnected channels and a vertically staggered cross-pore structure. Compared with the one-dimensional array honeycomb channel structure of traditional ceramic carriers, the interconnected channels of the carrier can fully expose the surface manganese-based active components, improve the reaction contact conditions, and improve the atomic utilization efficiency of the active components.
[0046] According to the present invention, preferably, based on 100 parts by mass of the photosensitive resin mixed liquid, it includes 1-12 parts of photoinitiator, 82-92 parts of photosensitive resin, and 3-7 parts of powder dispersant, and preferably includes 3-8 parts of photoinitiator, 88-92 parts of photosensitive resin, and 3-5 parts of powder dispersant.
[0047] In the present invention, the photosensitive resin mixed liquid is obtained by uniformly mixing a photoinitiator, a photosensitive resin and a powder dispersant. The mixing method is not particularly limited and those skilled in the art can adjust it as needed to obtain a uniformly mixed photosensitive resin mixed liquid.
[0048] According to the present invention, the photoinitiator can be a conventional photoinitiator in the art. Preferably, the photoinitiator is selected from at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (photoinitiator TPO), phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819) and isopropylthioxanthone (ITX).
[0049] According to the present invention, the specific composition of the photosensitive resin has a wide range of choices and can be selected according to conventional technical means in the art. Preferably, the photosensitive resin is a mixture of an acrylate prepolymer and an acrylate monomer, and the acrylate prepolymer is an epoxy acrylate prepolymer and / or a polyurethane acrylate prepolymer.
[0050] In the present invention, the acrylic ester monomer may be a conventional acrylic ester monomer in the art, and is preferably at least one selected from 1,6-hexanediol diacrylate (HDDA), tripropylene glycol diacrylate (TPGDA) and trimethylolpropane triacrylate (TMPTA).
[0051] In the present invention, the powder dispersant is a commonly used commercial dispersant, preferably at least one selected from sulfate ester powder dispersants, polyol powder dispersants, polyurethane powder dispersants and silane coupling agent powder dispersants.
[0052] According to the present invention, preferably, the mass ratio of the acrylate prepolymer to the acrylate monomer in the photosensitive resin is 1:0.5-2.3, for example, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.2, 1:1.4, 1:1.5, 1:1.6, 1:1.8, 1:2, 1:2.2, 1:2.3, and any range between any two values, preferably 1:0.8-1.5.
[0053] According to the present invention, preferably, in step (1), the mass ratio of the ceramic powder to the photosensitive resin mixture is 1:0.2-1.5, such as 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.5, and any range between any two values, preferably 1:0.5-1.4. The photosensitive ceramic slurry obtained by mixing according to the above mass ratio has a fast curing speed when 3D printing is subsequently performed, and the structural stability of the carrier material obtained after sintering is better.
[0054] In the present invention, the mixing method of the photosensitive resin mixed liquid and the ceramic powder is not particularly limited, and the photosensitive resin mixed liquid and the ceramic powder are evenly mixed to obtain a photosensitive ceramic slurry. According to a preferred embodiment of the present invention, the photosensitive resin mixed liquid is placed in a high-speed disperser, and the ceramic powder is slowly poured in. During the process, the high-speed disperser is turned on for stirring, and the stirring rate is 400-650rpm / min. When the ceramic powder is completely poured in, continue stirring for 20-60min to obtain a preliminarily mixed photosensitive ceramic slurry. The above slurry is repeatedly ground in a ball mill for 3-5 times, each grinding time is 0.5-2h, and the rotation speed is 100-500rpm, and the photosensitive ceramic slurry is ground.
[0055] In the present invention, the type of the ball mill is not particularly limited, and can be a conventional ball mill in the art. Preferably, a planetary ball mill is used.
[0056] According to the present invention, preferably, the ceramic powder is a natural aluminosilicate mineral clay, preferably at least one selected from cordierite, kaolin and bentonite.
[0057] According to the present invention, there is no particular limitation on the average particle size of the ceramic powder. Preferably, the average particle size of the ceramic powder is less than 10 μm, preferably 2.5-5 μm. The use of ceramic powder with an average particle size less than 10 μm is more conducive to uniformly mixing the photosensitive resin mixture with the ceramic powder, obtaining a photosensitive ceramic slurry with better dispersion, fast curing speed during 3D printing, and high production efficiency. If the particles of the ceramic powder are large, it is preferred to further improve their uniformity through subsequent ball milling.
[0058] In the present invention, a printing body is prepared by 3D printing, a three-dimensional structure is designed using modeling software, a photosensitive ceramic slurry is placed in a 3D printer material cylinder, a three-dimensional model is introduced, and 3D printing is performed after computer slicing to obtain a printing body with a connected pore structure.
[0059] In the present invention, preferably, a modeling software is used for three-dimensional structure design, and the modeling software is selected from SolidWorks, 3DMAX, AutoCAD or Materialise Magics.
[0060] According to the present invention, preferably, the 3D printing conditions include: single layer curing thickness 20-150 μm, single layer illumination time 5-20 s, illumination intensity 2-10 mW / cm 2 .
[0061] In the present invention, the "printed blank" is a general term for the prepared blanks. The printing method can be used to customize complex three-dimensional structures suitable for different scenarios. It does not rely on molds, nor does it require complex post-processing of the carrier. The interconnected channel structure of the carrier is simple and controllable. Compared with traditional material processing technology, it has the characteristics of high raw material utilization, strong structural design, and high flexibility in structural adjustment. It is an ideal method for designing three-dimensional cross-linked channel carrier materials.
[0062] In the present invention, there is no particular limitation on the size and structure of the printed body, and those skilled in the art can make appropriate selections according to the specific application scenarios of the prepared catalyst. The present invention subsequently provides a specific preferred embodiment for use in a catalytic oxidation catalyst, but the present invention is not limited thereto.
[0063] The present invention does not specifically limit the interconnected pore structure, which has the conventional meaning in the art. In the present invention, the interconnected pore structure refers to the cross-connected pores in the vertical and horizontal directions of the printed body, which have good permeability. There is no specific limitation on the distribution of the pores, and those skilled in the art can make adaptive selections based on the specific catalyst preparation conditions. The distribution of the pores can be uniform, symmetrical, or uneven, asymmetrical. According to a preferred embodiment of the present invention, the specific pore structure is as follows Figure 1 and Figure 2 shown.
[0064] According to the present invention, preferably, the printed body has a vertically staggered structure composed of cubic columns with a bottom side length of 0.5-2 mm. The printed body with the above structure is used as a carrier to prepare a manganese-based catalyst after being treated, which can effectively alleviate the problem of uneven airflow distribution and insufficient residence time of the raw material in the catalyst pores, and improve the reaction contact conditions.
[0065] In the present invention, the vertical staggered structure has the conventional meaning in the art, and refers to a mutually perpendicular structure formed by overlapping cubic columns, such as Figure 1 As shown. A cubic column refers to a column formed by two equal bases of squares and sides perpendicular to the bases. The base length refers to the length of the side of the base of the cubic column.
[0066] According to the present invention, the degreasing process of the printed body is not particularly limited, and those skilled in the art can make adaptive adjustments according to the degreasing conditions of the printed body, as long as the organic matter in the body is removed so that the inorganic material is solidified into a ceramic material. Preferably, the degreasing process of the printed body includes: a heating temperature of 400-800°C and a heating time of 1-10h.
[0067] Further preferably, in step (2), the degreasing of the printed body is divided into two stages:
[0068] In the first stage, the temperature is increased to 450-550°C at a rate of 3-8°C / min and maintained for 1-3h, preferably increased to 460-530°C at a rate of 3-7°C / min and maintained for 1.5-2.5h;
[0069] In the second stage, the temperature is further increased to 650-750°C at a rate of 8-15°C / min and maintained for 1-3h, preferably increased to 680-720°C at a rate of 8-12°C / min and maintained for 2-3h.
[0070] In the present invention, preferably, the degreasing is carried out in two stages. In the first stage, the heating temperature is controlled to be low and the heating rate is slow, so that the structure of the printed body can be kept intact while removing the organic matter in the printed body. The heating rate is controlled at 3-8°C / min to avoid excessive heating to cause cracks in the body. In the second stage, the heating temperature is increased to solidify the inorganic material in the printed body into porcelain.
[0071] According to the present invention, preferably, the sintering conditions include: sintering temperature of 1300-1600°C, preferably 1350-1500°C; sintering time of 1-3h, preferably 1.5-2.5h; heating rate of 8-15°C / min, preferably 9-12°C / min. In the present invention, sintering is carried out under the above sintering conditions to obtain a 3D printed ceramic carrier, which provides support for the subsequent in-situ generation of a manganese-based active component layer on the carrier.
[0072] According to the present invention, preferably, after sintering, the temperature is cooled to room temperature at a cooling rate of 3-8°C / min, preferably 4-6°C / min.
[0073] According to the present invention, preferably, in step (3), the volume ratio of the 3D printed ceramic carrier to the manganese-based precursor dispersion is 1:8-20, such as 1:8, 1:9, 1:10, 1:12, 1:15, 1:18, 1:20, and any range between any two values, preferably 1:9-15. In the present invention, limiting the volume ratio of the 3D printed ceramic carrier to the manganese-based precursor dispersion helps to control the growth rate of the manganese-based active component layer. Too fast a growth rate will cause uneven distribution of the active components, and too slow a growth rate will result in too long a catalyst synthesis time.
[0074] According to the present invention, preferably, the conditions of the hydrothermal reaction include: the reaction temperature is 90-160°C, such as 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, and any range between any two values, preferably 110-140°C; the reaction time is 12-24h, such as 12h, 14h, 16h, 18h, 20h, 22h, 24h, and any range between any two values, preferably 12-18h. Carrying out the hydrothermal reaction under the above conditions allows the manganese-based active components in the manganese-based precursor dispersion to be effectively loaded on the 3D printing ceramic carrier, thereby improving the atomic utilization efficiency of the active components.
[0075] According to the present invention, preferably, the manganese-based precursor dispersion comprises a manganese salt, an optional soluble salt of a M metal and a solvent, and the M metal is selected from at least one of Fe, Co, Ni, Cu and Ce.
[0076] In the present invention, preferably, the optional M metal is added in combination with the Mn element, which can enhance the redox ability of the catalyst through the close electron transfer process between the M metal and Mn. This synergistic effect further improves the catalytic oxidation activity of the in-situ grown manganese-based active component layer. Combined with a 3D printed ceramic carrier with a special structure, low-temperature and efficient oxidation of VOCs can be achieved.
[0077] According to the present invention, the type of the manganese salt is not particularly limited. Preferably, the manganese salt is selected from at least one of MnSO4, Mn(NO3)2, MnCl2 and Mn(CH3COO)2.
[0078] According to the present invention, preferably, the soluble salt of the M metal is selected from at least one of sulfates, nitrates, chlorides and acetates of the M metal.
[0079] According to the present invention, preferably, the M metal is selected from at least one of Co, Cu and Fe. More preferably, the M metal soluble salt is selected from at least one of Co(NO3)2, Cu(NO3)2 and Fe(NO3)2.
[0080] According to the present invention, preferably, the total molar concentration of Mn and optional M metal in the manganese-based precursor dispersion is 0.02-0.2 mol / L, for example, 0.02 mol / L, 0.04 mol / L, 0.06 mol / L, 0.08 mol / L, 0.1 mol / L, 0.12 mol / L, 0.14 mol / L, 0.16 mol / L, 0.18 mol / L, 0.2 mol / L, and any range between any two values, preferably 0.04-0.16 mol / L.
[0081] According to the present invention, preferably, the molar ratio of Mn to M metal in the manganese-based precursor dispersion is 1:0-1, such as 1:0, 1:0.02, 1:0.05, 1:0.1, 1:0.2, 1:0.3, 1:0.5, 1:0.8, 1:1, and any range between any two values, preferably 1:0.02-0.3. In the present invention, the molar ratio of Mn to M metal in the manganese-based precursor dispersion is limited to a certain range. If the proportion of M metal is too high, the main structure of manganese oxide cannot be maintained, and the redox property of the active component will be greatly reduced.
[0082] According to the present invention, preferably, in step (3), a precipitation aid is further added to the hydrothermal reaction, and the ratio of the total molar amount of Mn and M metals to the molar amount of the precipitation aid is 1:1-2.5, for example, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, 1:2.2, 1:2.4, 1:2.5, and any range between any two values, preferably 1:1.4-2.
[0083] According to the present invention, preferably, the precipitation aid is selected from at least one of easily hydrolyzed organic amines, soluble carbonates and soluble bicarbonates, preferably selected from at least one of urea, NH4HCO3 and (NH4)2CO3. In the present invention, the above-mentioned precipitation aid is added to the hydrothermal reaction, and the amount of the precipitation aid added is controlled at the same time, so that the loading amount of the manganese-based active component can be controlled, so that it slowly precipitates after the hydrothermal reaction begins, and is uniformly loaded on the carrier through in-situ growth. Too little precipitation aid addition will result in incomplete precipitation of the Mn element and the M metal element, and too much precipitation aid addition will cause material waste.
[0084] In the present invention, there is no particular limitation on the equipment for the hydrothermal reaction, as long as the reaction can be carried out under the hydrothermal reaction conditions, and those skilled in the art can select it as needed. According to a preferred embodiment of the present invention, the hydrothermal reaction is carried out in a reactor, preferably a Teflon reactor.
[0085] In the present invention, preferably, after the hydrothermal reaction is completed, the reactor is cooled (preferably to room temperature) and then opened. This preferred embodiment avoids the safety hazard of opening the reactor at high temperature due to the self-generated pressure in the reactor caused by the hydrothermal reaction under elevated temperature.
[0086] In the present invention, preferably, after the hydrothermal reaction is completed, the step of separating and rinsing the 3D printed ceramic carrier of the in-situ grown manganese-based active component layer is also included. There is no particular limitation on the separation method, and those skilled in the art can make adaptive adjustments as long as the carrier is separated from the manganese-based precursor dispersion. There is no particular limitation on the rinsing method, and those skilled in the art can make adaptive adjustments according to the effect of the rinsing. According to a preferred embodiment of the present invention, deionized water is used for rinsing.
[0087] According to the present invention, preferably, in step (3), the roasting conditions include: a roasting temperature of 300-650°C, preferably 350-550°C; and a roasting time of 1.5-4h, preferably 2-3.5h.
[0088] According to the present invention, preferably, in order to obtain a manganese-based active component layer with MnO2 as the main phase, the temperature is increased to 300-450°C at a rate of 1-5°C / min and maintained for 1.5-4h.
[0089] According to the present invention, preferably, in order to obtain a manganese-based active component layer with Mn2O3 as the main phase, the temperature is increased to 450-650°C at a rate of 1-5°C / min and maintained for 1.5-4h.
[0090] In the present invention, different phases of manganese-based active component layers can be obtained by different calcination conditions. When MnO2 is the main phase, the catalyst has a strong redox ability, but is not resistant to high temperatures and is suitable for treating VOCs with low oxidation difficulty at low temperatures. When Mn2O3 is the main phase, the catalyst has a high thermal stability and is suitable for treating VOCs with high oxidation difficulty.
[0091] The fourth aspect of the present invention provides a manganese-based catalyst prepared by the method described in the third aspect.
[0092] According to the present invention, preferably, the manganese-based catalyst comprises a 3D printed ceramic carrier and a manganese-based active component in-situ grown on the 3D printed ceramic carrier.
[0093] In the present invention, preferably, based on the volume of the 3D printed ceramic carrier of 1L, the content of the manganese-based active component layer grown in situ on the 3D printed ceramic carrier is 30-150g / L, such as 30g, 40g, 50g, 60g, 70g, 80g, 90g, 100g, 110g, 120g, 130g, 140g, 150g, and any range composed of any two values, preferably 50-140g / L. In the present invention, the manganese-based active component is loaded on the surface of the 3D printed ceramic carrier to replace the precious metal active component, which effectively reduces the catalyst cost while ensuring the excellent catalytic oxidation activity of the catalyst.
[0094] In the present invention, the volume of the 3D printed ceramic carrier is calculated according to the outer dimensions of the carrier obtained by 3D printing.
[0095] The fifth aspect of the present invention provides a use of the manganese-based catalyst described in the second aspect or the fourth aspect in a catalytic oxidation reaction.
[0096] In the present invention, preferably, the manganese-based catalyst is used in the catalytic oxidation reaction of VOCs.
[0097] In the present invention, there is no particular limitation on the composition of the VOCs, which are conventional volatile organic compounds in the art, including at least one of alkanes (straight-chain alkanes and cycloalkanes), olefins, alkynes, benzene series, alcohols, aldehydes, ethers, ketones, acids, esters and halogenated hydrocarbons.
[0098] In the present invention, the above-mentioned manganese-based catalyst is used to carry out the catalytic oxidation reaction of VOCs, which can effectively alleviate the problems of uneven airflow distribution and insufficient residence time of VOCs in the catalyst pores, improve the reaction contact conditions, and reduce the VOCs gas conversion temperature.
[0099] In the present invention, preferably, the manganese-based catalyst is used in the catalytic oxidation reaction of alkanes, more preferably in the catalytic oxidation reaction of propane.
[0100] In the present invention, the catalytic oxidation reaction device is not particularly limited and can be selected from conventional reaction devices in the art. According to a preferred embodiment of the present invention, the catalytic oxidation reaction is carried out in a fixed bed reaction device.
[0101] In the present invention, the reaction conditions of the catalytic oxidation are not particularly limited, and those skilled in the art can make adaptive adjustments according to the conditions of the catalytic oxidation reaction. Preferably, the reaction conditions include: the reaction pressure is normal pressure, the reaction temperature is 100-600°C, preferably 200-500°C, the volume space velocity is 1000-80000h -1 , preferably 10000-50000h -1 .
[0102] According to a particularly preferred embodiment of the present invention, a method for preparing a manganese-based catalyst by 3D printing comprises the following steps:
[0103] (1) mixing a photosensitive resin mixed liquid with a ceramic powder to obtain a photosensitive ceramic slurry, and performing 3D printing to obtain a printed body;
[0104] (2) degreasing and sintering the printed body to obtain a 3D printed ceramic carrier;
[0105] (3) subjecting the 3D printed ceramic support to a hydrothermal reaction in a manganese-based precursor dispersion, and calcining to obtain a manganese-based catalyst;
[0106] The conditions of the hydrothermal reaction include: reaction temperature of 110-140°C; reaction time of 12-18h;
[0107] The molar ratio of Mn to M metal in the manganese-based precursor dispersion is 1:0.02-0.3;
[0108] In step (3), a precipitation aid is also added to the hydrothermal reaction, and the ratio of the total molar amount of Mn and M metal to the molar amount of the precipitation aid is 1:1.4-2.
[0109] The present invention will be described in detail below through examples and comparative examples. In the following examples and comparative examples, the room temperature is 25°C;
[0110] The three-dimensional model is established by 3DMAX;
[0111] The 3D printing is completed by a sinking DLP-3D printer (model SU136A) of Foshan Guanglei Intelligent Manufacturing Co., Ltd.
[0112] The planetary ball mill is a JC-QM series vertical planetary ball mill of Juchuang Environmental Protection;
[0113] The average particle size of the ceramic powder is the equivalent volume diameter obtained by laser particle size method, and the test instrument is Malvern Mastersizer 3000.
[0114] Example 1
[0115] (1-1) Prepare photosensitive resin mixture:
[0116] Epoxy acrylate prepolymer (Foshan Guanglei Intelligent Manufacturing Co., Ltd.) and 1,6-hexanediol diacrylate (HDDA) were mixed in a mass ratio of 1:1.5, and the mixture was stirred evenly to obtain a photosensitive resin. 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and a powder dispersant (Yangzhou Lida Resin Co., Ltd., LD-1241) were added thereto so that every 100 parts by weight of the photosensitive resin mixed liquid contained 5 parts of photoinitiator, 92 parts of photosensitive resin, and 3 parts of powder dispersant. The photosensitive resin mixed liquid was stirred evenly to obtain a photosensitive resin mixed liquid.
[0117] (1-2) Preparation of photosensitive ceramic slurry:
[0118] Place the photosensitive resin mixture prepared in (1-1) in a high-speed disperser, weigh the required amount of cordierite powder (Jushi Mineral Products Processing Plant, Lingshou County, Hebei Province, average particle size 4.5μm), and the mass ratio of ceramic powder to photosensitive resin mixture is 1:1. Slowly pour it into the photosensitive resin mixed solution, turn on the high-speed disperser for stirring during the pouring process, and set the stirring rate of the high-speed disperser to 500rpm. When the ceramic powder is completely poured in, continue stirring for 40min. Use a planetary ball mill to repeatedly grind the obtained preliminary mixed ceramic slurry 4 times, each grinding time is 1h, and the rotation speed is 300rpm to obtain a photosensitive ceramic slurry.
[0119] (1-3) 3D printing:
[0120] The photosensitive ceramic slurry was placed in a material tank, imported into a three-dimensional model, sliced and 3D printed to obtain a printed body with a connected channel structure. The printed body has a vertical staggered structure composed of cubic columns with a side length of 1.2 mm, and a cylindrical shape with a bottom diameter of 3 cm and a height of 1 cm. The 3D printing parameters are as follows: single-layer curing thickness 100 μm, single-layer illumination time 10 s, and illumination intensity 5 mW / cm 2 The printing blank has Figure 1 Similar pore structure.
[0121] (2) Degreasing and sintering of printed body:
[0122] Two-stage heating treatment was used for degreasing. In the first stage, the temperature was raised to 500°C at a rate of 5°C / min and maintained for 2h; in the second stage, the temperature was further raised to 700°C at a rate of 10°C / min and maintained for 2h.
[0123] After the degreasing treatment is completed, the temperature is continued to be raised for sintering, and the temperature is continued to be raised to 1400°C at a rate of 10°C / min and maintained for 2 hours; then the temperature is lowered to room temperature at a rate of 5°C / min to obtain a 3D printed ceramic carrier.
[0124] (3-1) In-situ growth of manganese-based active component layer: 1.73 g of an aqueous solution containing 50 wt% Mn(NO3)2 was diluted in 80 mL of deionized water to obtain a manganese-based precursor dispersion, which was transferred to a 100 mL Teflon reactor, and 0.58 g of urea was added and stirred for 30 min. The 3D printed ceramic carrier was completely immersed in the manganese-based precursor dispersion, and the reactor was sealed and reacted at 120°C for 12 h. After the reaction was completed, the carrier was separated from the liquid phase and rinsed with deionized water.
[0125] (3-2) Post-treatment: The 3D printed ceramic support with the in-situ grown manganese-based active component layer was dried at 120°C for 2 h, then heated to 350°C at a rate of 3°C / min and maintained for 3 h to obtain a manganese-based catalyst. Figure 2This is a photo of the manganese-based catalyst prepared in Example 1. The loading amount of the manganese-based active component is shown in Table 1.
[0126] Example 2
[0127] (1-1) Prepare photosensitive resin mixture:
[0128] Polyurethane acrylate (Foshan Guanglei Intelligent Manufacturing Co., Ltd.) and trimethylolpropane triacrylate (TMPTA) were mixed in a mass ratio of 1:2 and stirred well to obtain a photosensitive resin. Isopropyl thioxanthone (ITX) and a powder dispersant (Yangzhou Lida Resin Co., Ltd., LD-1800) were added thereto so that 8 parts of photoinitiator, 88 parts of photosensitive resin and 4 parts of powder dispersant were contained in every 100 parts by weight of the photosensitive resin mixed solution, and the photosensitive resin mixed solution was obtained after stirring well.
[0129] (1-2) Preparation of photosensitive ceramic slurry:
[0130] Place the photosensitive resin mixture prepared in (1-1) in a high-speed disperser, weigh the required amount of bentonite powder (Jushi Mineral Products Processing Plant, Lingshou County, Hebei Province, average particle size 3.6 μm), and slowly pour it into the photosensitive resin mixed solution. The mass ratio of ceramic powder to photosensitive resin mixed solution is 1:1.4. Turn on the high-speed disperser for stirring during the pouring process, and set the stirring rate of the high-speed disperser to 600 rpm. When the ceramic powder is completely poured in, continue stirring for 60 minutes. The obtained preliminary mixed ceramic slurry is repeatedly ground 3 times using a planetary ball mill, each grinding time is 1.5 hours, and the rotation speed is 450 rpm to obtain a photosensitive ceramic slurry.
[0131] (1-3) 3D printing:
[0132] The ceramic 3D slurry was placed in a material tank, imported into a 3D model, sliced and 3D printed to obtain a printed body with a connected channel structure. The printed body has a vertical staggered structure composed of cubic columns with a side length of 1.8 mm, a cylindrical shape, a bottom diameter of 3 cm, and a height of 1 cm. The 3D printing parameters are as follows: single layer curing thickness 125 μm, single layer illumination time 15 s, illumination intensity 8 mW / cm 2 .
[0133] (2) Degreasing and sintering of printed body:
[0134] Two-stage heating treatment is used for debinding. In the first stage, the temperature is raised to 530°C at a rate of 7°C / min and maintained for 2h; in the second stage, the temperature is further raised to 720°C at a rate of 12°C / min and maintained for 2.5h. After the debinding treatment is completed, the temperature is continued to be raised for sintering, and the temperature is further raised to 1500°C at a rate of 10°C / min and maintained for 1.5h; then the temperature is lowered to room temperature at a rate of 5°C / min to obtain a 3D printed ceramic carrier.
[0135] (3-1) In-situ growth of manganese-based active component layer:
[0136] 1.08g of MnSO4·H2O and 0.15g of Co(NO3)2·6H2O were dissolved in 80mL of deionized water to obtain a manganese-based precursor dispersion, which was transferred to a 100mL Teflon reactor, and 0.77g of urea was added and stirred for 30min. The 3D printed ceramic carrier was completely immersed in the manganese-based precursor dispersion, and the reactor was sealed and reacted at 120°C for 12h. After the reaction was completed, the carrier was separated from the liquid phase and rinsed with deionized water.
[0137] (3-2) Post-treatment: The 3D printed ceramic support with the in-situ grown manganese-based active component layer was dried at 120 °C for 2 h, then heated to 400 °C at a rate of 3 °C / min and maintained for 3 h to obtain a manganese-based catalyst. The manganese-based active component loading is shown in Table 1.
[0138] Example 3
[0139] (1-1) Prepare photosensitive resin mixture:
[0140] Polyurethane acrylate (Foshan Guanglei Intelligent Manufacturing Co., Ltd.) and tripropylene glycol diacrylate (TPGDA) were mixed in a mass ratio of 1:0.8 and stirred thoroughly to obtain a photosensitive resin. Phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819) and powder dispersant (Yangzhou Lida Resin Co., Ltd., LD-1800) were added thereto so that 3 parts of photoinitiator, 92 parts of photosensitive resin and 5 parts of powder dispersant were contained in every 100 parts by weight of the photosensitive resin mixed solution, and the photosensitive resin mixed solution was obtained after being stirred thoroughly.
[0141] (1-2) Preparation of photosensitive ceramic slurry:
[0142] Place the photosensitive resin mixture obtained in (1-1) in a high-speed disperser. Weigh the required amount of kaolin powder (Jushi Mineral Products Processing Plant, Lingshou County, Hebei Province, average particle size 2.8μm), slowly pour it into the photosensitive resin mixed solution, the mass ratio of ceramic powder to photosensitive resin mixed solution is 1:0.5, turn on the high-speed disperser for stirring during the pouring process, and set the stirring rate of the high-speed disperser to 400rpm. When the ceramic powder is completely poured in, continue stirring for 25min. Use a planetary ball mill to repeatedly grind the obtained preliminary mixed ceramic slurry 5 times, each grinding time is 0.8h, and the rotation speed is 450rpm to obtain a photosensitive ceramic slurry.
[0143] (1-3) 3D printing:
[0144] The photosensitive ceramic slurry was placed in a material tank, imported into a three-dimensional model, sliced and 3D printed to obtain a printed body with a connected channel structure. The printed body has a vertical staggered structure composed of cubic columns with a side length of 0.8 mm, a cylindrical shape, a bottom diameter of 3 cm, and a height of 1 cm. The 3D printing parameters are as follows: single layer curing thickness 40 μm, single layer illumination time 15 s, illumination intensity 3 mW / cm 2 .
[0145] (2) Degreasing and sintering of printed body:
[0146] Debinding is performed by two-stage heating treatment. In the first stage, the temperature is raised to 460°C at a rate of 3°C / min and maintained for 2 hours; in the second stage, the temperature is further raised to 680°C at a rate of 8°C / min and maintained for 3 hours. After the debinding treatment is completed, the temperature is further raised to 1350°C at a rate of 10°C / min and maintained for 2 hours; then the temperature is lowered to room temperature at a rate of 5°C / min.
[0147] (3-1) In-situ growth of manganese-based active component layer: 1.63 g of MnSO4·H2O and 0.56 g of Cu(NO3)2·3H2O were dissolved in 80 mL of deionized water to obtain a manganese-based precursor dispersion, which was transferred to a 100 mL Teflon reactor, 1.08 g of urea was added and stirred for 30 min, and the 3D printed ceramic carrier was completely immersed in the manganese-based precursor dispersion. The reactor was sealed and reacted at 120°C for 12 h. After the reaction was completed, the carrier was separated from the liquid phase and rinsed with deionized water.
[0148] (3-2) Post-treatment: The 3D printed ceramic support with the in-situ grown manganese-based active component layer was dried at 120 °C for 2 h, then heated to 500 °C at a rate of 3 °C / min and maintained for 3 h to obtain a manganese-based catalyst. The manganese-based active component loading is shown in Table 1.
[0149] Example 4
[0150] A manganese-based catalyst was prepared according to the method of Example 3, except that 0.77 g of urea was added in step (3). Other conditions were the same as those of Example 3 to obtain a manganese-based catalyst. The loading amount of the manganese-based active component is shown in Table 1.
[0151] Example 5
[0152] A manganese-based catalyst was prepared according to the method of Example 3, except that the conditions of the hydrothermal reaction in step (3) were reaction temperature 90° C. and reaction time 11 h. The manganese-based catalyst was obtained. The loading amount of the manganese-based active component is shown in Table 1.
[0153] Example 6
[0154] A manganese-based catalyst was prepared according to the method of Example 3, except that urea was not added in step (3). The manganese-based catalyst was prepared. The loading amount of the manganese-based active component is shown in Table 1.
[0155] Example 7
[0156] A manganese-based catalyst was prepared according to the method of Example 3. In step (3), 1.01 g of MnSO4·H2O and 1.45 g of Cu(NO3)2·3H2O were dissolved in 80 mL of deionized water to obtain a manganese-based precursor dispersion. The amount of urea added was adjusted. The ratio of the total molar amount of Mn and M metal to the molar amount of urea was the same as that in Example 3. Other conditions were the same as those in Example 3 to obtain a manganese-based catalyst. The loading amount of manganese-based active components is shown in Table 1.
[0157] Example 8
[0158] (1) The carrier adopts a customized commercial cordierite carrier (Jiangxi Guoci Environmental Protection Technology Co., Ltd., ceramic honeycomb carrier) with a bulk density of 0.5 kg / L, a pore volume of 0.5 mL / g, and a single cubic column straight channel inside; it is cut into a cylinder with a bottom diameter of 3 cm and a height of 1 cm.
[0159] (2) According to the method of step (3) of Example 3, in-situ growth and post-treatment of a manganese-based active component layer were carried out to prepare a manganese-based catalyst. The loading amount of the manganese-based active component is shown in Table 1.
[0160] Comparative Example 1
[0161] (1) Carry out steps (1) and (2) according to the method of Example 3;
[0162] (2) MnO2 powder was added to deionized water, and then 63% concentrated nitric acid was added to adjust the pH of the system to less than 4. The mixed solution was fully ground using a vibrating ball mill (Tianjin Shengyuan Equipment Co., Ltd., GZM-6). The grinding conditions were: ball milling time 3 h, rotation speed 800 rpm, and the average diameter of the MnO2 particles in the mixed solution was 8 μm, and the MnO2 content in the mixed solution was 15 wt%;
[0163] (3) The ground mixed solution was evenly coated on the surface of the 3D printing ceramic carrier, and then dried and calcined. The total coating amount on each liter of the 3D printing ceramic carrier was 60 g / L. The drying and calcining conditions were the same as those in Example 3. The loading amount of the manganese-based active component is shown in Table 1.
[0164] Comparative Example 2
[0165] (1) A customized commercial cordierite carrier (Jiangxi Guoci Environmental Protection Technology Co., Ltd., ceramic honeycomb carrier) with a bulk density of 0.5 kg / L, a pore volume of 0.5 mL / g, and a single cubic column straight channel inside was cut into a cylinder with a bottom diameter of 3 cm and a height of 1 cm;
[0166] (2) Add an appropriate amount of Al2O3 powder to deionized water, then add 63% concentrated nitric acid to adjust the system to a pH value of less than 4, and use a vibrating ball mill (Tianjin Shengyuan Equipment Co., Ltd., GZM-6) to fully grind the above mixed solution. The grinding conditions are: ball milling time 1.5h, speed 1200rpm. The average diameter of Al2O3 particles in the mixed solution after grinding is 12.5μm. After stirring the ball-milled mixed solution for 2 hours, add an appropriate amount of precious metal Na2PdCl4 solution, continue stirring for 2 hours to obtain a catalyst slurry, and control the solid content of the slurry to 15wt%.
[0167] (3) The catalyst slurry was coated on the carrier of step (1). The total active component loading in the coating was 22 g / L, of which the Pd content was 0.15 g / L and the rest was Al2O3. After coating, post-treatment was performed. The post-treatment conditions were the same as those in Example 3. The active component loading is shown in Table 1.
[0168] Comparative Example 3
[0169] (1) A customized commercial cordierite carrier (Jiangxi Guoci Environmental Protection Technology Co., Ltd., ceramic honeycomb carrier) with a bulk density of 0.5 kg / L, a pore volume of 0.5 mL / g, and a single cubic column straight channel inside was used; it was cut into a cylinder with a bottom diameter of 3 cm and a height of 1 cm;
[0170] (2) A certain amount of MnO2 powder was added to deionized water, and then 63% concentrated nitric acid was added to adjust the pH of the mixture to less than 4. The mixture was fully ground using a vibrating ball mill (Tianjin Shengyuan Equipment Co., Ltd., GZM-6). The specific grinding conditions were: ball milling time 3h, speed 800rpm. The average diameter of MnO2 particles in the mixed solution after ball milling was 8μm, and the solid content of the slurry was controlled to be 15wt%;
[0171] (3) The mixed solution was evenly coated on the surface of a commercial cordierite carrier and post-treated. The post-treatment was the same as in Example 3. The loading amount of the manganese-based active component is shown in Table 1.
[0172] Comparative Example 4
[0173] (1) preparing a photosensitive ceramic slurry according to the conditions of steps (1-1) and (1-2) in Example 3;
[0174] (2) diluting 1.73 g of an aqueous solution containing 50 wt% Mn(NO3)2 in 80 mL of deionized water to obtain a manganese-based precursor dispersion, and mixing the obtained manganese-based precursor dispersion with the photosensitive ceramic slurry in step (1) at a mass ratio of the manganese-based precursor dispersion to the photosensitive ceramic slurry of 1:20 to obtain a mixed slurry;
[0175] (3) The mixed slurry is 3D printed to obtain a catalyst precursor, and the catalyst precursor is calcined under the same calcination conditions as in Example 3.
[0176] Test Case
[0177] The catalytic oxidation activity of the catalyst was evaluated by the catalytic oxidation reaction of propane, which was carried out on a micro-fixed bed reactor designed and manufactured by Tianjin Pengxiang Technology Co., Ltd. and equipped with a Multigas 2030 infrared detector from MKS. The reaction was carried out at normal pressure, with an initial temperature of 250°C and a temperature program of 5°C / min to 500°C. The inlet gas volume composition was 600ppmv propane + 21% O2 + 79% N2, and the volume space velocity was 26000h -1 , the results are shown in Table 1.
[0178] The active component loading is based on the mass of manganese oxide and metal oxide.
[0179] Table 1
[0180] serial number <![CDATA[Propane T 50 (℃)]]> <![CDATA[Propane T 90 (℃)]]> Active ingredient loading (g / L) Example 1 332.5 420.3 61 Example 2 320.1 406.2 88 Example 3 301.3 390.5 132 Example 4 312.7 402.3 97 Example 5 329.4 420.7 75 Example 6 342.5 432.2 24 Example 7 325.1 412.5 128 Example 8 338.7 422.4 120 Comparative Example 1 350.6 451.2 60 Comparative Example 2 413.5 >500 <![CDATA[22(Pd+Al2O3)]]> Comparative Example 3 386.5 480.6 26 Comparative Example 4 >500 >500 0(no coating)
[0181] Note: 50 is the temperature when the propane conversion rate is 50%, T 90 It is the temperature corresponding to the propane conversion rate of 90%, and the propane conversion rate = 1-(remaining propane content / propane raw material content) × 100%.
[0182] From the results in Table 1, it can be seen that the embodiment of the present invention in which the manganese-based active component is grown in situ on a regular carrier has a significantly better effect than the traditional cordierite carrier coated with the manganese-based active component, and the effect is better than the traditional cordierite-supported precious metal Pd catalyst, and can significantly reduce the propane conversion temperature. Compared with the traditional regular carrier, the 3D printed carrier has three-dimensional interconnected channels, which can further improve the catalytic oxidation activity, and the conversion temperature is lower at the same propane conversion rate.
[0183] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a manganese-based catalyst, characterized in that: The following steps are involved: The structured support is subjected to a hydrothermal reaction in a manganese-based precursor dispersion, and calcined to obtain a manganese-based catalyst; The manganese-based precursor dispersion comprises a manganese salt, an optional soluble salt of M metal and a solvent, and a precipitation aid is optionally added; the M metal element is selected from at least one of Fe, Co, Ni, Cu and Ce.
2. The preparation method according to claim 1, wherein The conditions of the hydrothermal reaction include: reaction temperature of 90-160°C, preferably 110-140°C; reaction time of 12-24h, preferably 12-18h; Preferably, the volume ratio of the structured support to the manganese-based precursor dispersion is 1:8-20, preferably 1:9-15; Preferably, the precipitation aid is selected from at least one of an easily hydrolyzable organic amine, a soluble carbonate and a soluble bicarbonate, preferably selected from at least one of urea, NH4HCO3 and (NH4)2CO3; Preferably, the ratio of the total molar amount of the Mn and M metals to the molar amount of the precipitation aid is 1:1-2.5, preferably 1:1.4-2; Preferably, the total molar concentration of Mn and the optional M metal in the manganese-based precursor dispersion is 0.02-0.2 mol / L, preferably 0.04-0.16 mol / L; Preferably, the molar ratio of Mn to M metal in the manganese-based precursor dispersion is 1:0-1, preferably 1:0.02-0.
3.
3. A manganese-based catalyst, characterized in that The catalyst comprises a structured carrier and an active component layer loaded on the surface of the structured carrier, wherein the active component layer comprises a manganese compound and an optional M metal; Preferably, the M metal element is selected from at least one of Fe, Co, Ni, Cu and Ce; Preferably, based on the volume of the structured carrier as 1 L, the content of the active component layer on the surface of the structured carrier is 30-150 g / L, preferably 50-140 g / L; Preferably, the molar ratio of Mn to M metal in the active component layer is 1:0-1, preferably 1:0.02-0.
3.
4. A method for preparing a manganese-based catalyst by 3D printing, characterized in that: The following steps are involved: (1) mixing a photosensitive resin mixed liquid with a ceramic powder to obtain a photosensitive ceramic slurry, and performing 3D printing to obtain a printed body; (2) degreasing and sintering the printed body to obtain a 3D printed ceramic carrier; (3) subjecting the 3D printed ceramic carrier to a hydrothermal reaction in a manganese-based precursor dispersion and calcining to obtain a manganese-based catalyst.
5. The method according to claim 4, wherein: Based on 100 parts by mass of the photosensitive resin mixed liquid, it includes 1-12 parts of photoinitiator, 82-92 parts of photosensitive resin, and 3-7 parts of powder dispersant, preferably includes 3-8 parts of photoinitiator, 88-92 parts of photosensitive resin, and 3-5 parts of powder dispersant; Preferably, the photoinitiator is selected from at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and isopropylthioxanthone; Preferably, the photosensitive resin is a mixture of an acrylate prepolymer and an acrylate monomer, and the acrylate prepolymer is an epoxy acrylate prepolymer and / or a polyurethane acrylate prepolymer; Preferably, the mass ratio of the acrylate prepolymer to the acrylate monomer in the photosensitive resin is 1:0.5-2.3, preferably 1:0.8-1.
5.
6. The method according to claim 4 or 5, wherein: In step (1), the mass ratio of the ceramic powder to the photosensitive resin mixture is 1:0.2-1.5, preferably 1:0.5-1.4; Preferably, the ceramic powder is a natural aluminosilicate mineral clay, preferably at least one selected from cordierite, kaolin and bentonite; Preferably, the average particle size of the ceramic powder is less than 10 μm, preferably 2.5-5 μm.
7. The method according to any one of claims 4 to 6, wherein: The 3D printing conditions include: single layer curing thickness 20-150 μm, single layer illumination time 5-20 s, illumination intensity 2-10 mW / cm 2 ; Preferably, the printed body has a vertically staggered structure consisting of cubic columns with a bottom side length of 0.5-2 mm.
8. The method according to any one of claims 4 to 7, wherein: In step (2), the process of degreasing the printed body includes: heating at a temperature of 400-800° C. and a heating time of 1-10 h; Preferably, the degreasing of the printed body is divided into two stages: in the first stage, the temperature is increased to 450-550°C at a rate of 3-8°C / min and maintained for 1-3h, preferably increased to 460-530°C at a rate of 3-7°C / min and maintained for 1.5-2.5h; In the second stage, the temperature is further increased to 650-750°C at a rate of 8-15°C / min and maintained for 1-3h, preferably increased to 680-720°C at a rate of 8-12°C / min and maintained for 2-3h; Preferably, the sintering conditions include: sintering temperature of 1300-1600°C, preferably 1350-1500°C; sintering time of 1-3h, preferably 1.5-2.5h; heating rate of 8-15°C / min, preferably 9-12°C / min; Preferably, after sintering, the temperature is cooled to room temperature at a cooling rate of 3-8°C / min, preferably 4-6°C / min.
9. The method according to any one of claims 4 to 8, wherein: In step (3), the volume ratio of the 3D printing ceramic carrier to the manganese-based precursor dispersion is 1:8-20, preferably 1:9-15; Preferably, the conditions of the hydrothermal reaction include: reaction temperature of 90-160°C, preferably 110-140°C; reaction time of 12-24h, preferably 12-18h; Preferably, the manganese-based precursor dispersion comprises a manganese salt, an optional soluble salt of a M metal and a solvent, wherein the M metal element is selected from at least one of Fe, Co, Ni, Cu and Ce.
10. The method according to claim 9, wherein: The manganese salt is selected from at least one of MnSO4, Mn(NO3)2, MnCl2 and Mn(CH3COO)2; Preferably, the soluble salt of the M metal is selected from at least one of the sulfate, nitrate, chloride and acetate of the M metal; Preferably, the M metal is selected from at least one of Co, Cu and Fe; Preferably, the total molar concentration of Mn and the optional M metal in the manganese-based precursor dispersion is 0.02-0.2 mol / L, preferably 0.04-0.16 mol / L; Preferably, the molar ratio of Mn to M metal in the manganese-based precursor dispersion is 1:0-1, preferably 1:0.02-0.
3.
11. The method according to claim 9 or 10, wherein: In step (3), a precipitation aid is also added to the hydrothermal reaction, and the ratio of the total molar amount of Mn and M metal to the molar amount of the precipitation aid is 1:1-2.5, preferably 1:1.4-2; Preferably, the precipitation aid is selected from at least one of easily hydrolyzable organic amines, soluble carbonates and soluble bicarbonates, preferably selected from at least one of urea, NH4HCO3 and (NH4)2CO3.
12. The method according to any one of claims 4 to 11, wherein: In step (3), the calcination conditions include: calcination temperature of 300-650°C; calcination time of 1.5-4h; Preferably, in order to obtain a manganese-based active component layer with MnO2 as the main phase, the temperature is increased to 300-450°C at a rate of 1-5°C / min and maintained for 1.5-4h; Preferably, in order to obtain a manganese-based active component layer with Mn2O3 as the main phase, the temperature is increased to 450-650°C at a rate of 1-5°C / min and maintained for 1.5-4h.
13. A manganese-based catalyst prepared by the method according to any one of claims 4 to 12; Preferably, the manganese-based catalyst comprises a 3D printed ceramic carrier and a manganese-based active component in-situ grown on the 3D printed ceramic carrier.
14. Use of the manganese-based catalyst according to claim 3 or 13 in catalytic oxidation reactions.
Citation Information
Patent Citations
Square ceramic honeycomb carrier
CN104213961A
Water treatment material and application thereof
CN107552067A
Method for preparing structured catalyst carrier through photocuring
CN111760596A
Spherical denitration catalyst with lattice structure prepared by 3D printing and preparation method thereof
CN112536026A
Catalyst capable of promoting generation of singlet oxygen as well as preparation method and application of catalyst
CN115106079A
Cited By
Aluminum oxide catalyst with metal monatomic supported bionic bicontinuous amplitude-modulated decomposition structure as well as preparation method and application of aluminum oxide catalyst
CN120079372A